The fail-safe system to rescue the stalled ribosomes in Escherichia coli - Abo, Tatsuhiko; Chadani, Yuhei (Frontiers in Microbiology, 2014)
Translation terminates at stop codon. Without stop codon, ribosome cannot terminate translation properly and reaches and stalls at the 3' end of the mRNA lacking stop codon. Bacterial tmRNA-mediated trans-translation releases such stalled ribosome and targets the protein product to degradation by adding specific "degradation tag". Recently two alternative ribosome rescue factors, ArfA (YhdL) and ArfB (YaeJ), have been found in Escherichia coli. These three ribosome rescue systems are different each other in terms of molecular mechanism of ribosome rescue and their activity, but they are mutually related and co-operate to maintain the translation system in shape. This suggests the biological significance of ribosome rescue.